The Effect of Types of Biogas and Methanol Purification and Loading as Fuel for Four-Stroke Generators on Exhaust Emissions - I Wayan Angga Widianta Putra; I Gusti Ketut Sukadana; I Gusti Ngurah Putu Tenaya; I Putu Widiarta (Natural Sciences Engineering and Technology Journal, 2023)
Biogas is a type of new renewable energy that is formed through the fermentation process of organic waste materials, such as livestock manure, organic waste, and other materials by methanogenic bacteria in anaerobic (without oxygen) conditions. Methanol is a very light, volatile, colorless, tasteless, flammable, toxic liquid with a very faint odour. In addition, methanol can be used as a solvent and also as an alternative fuel. This study aimed to determine the effect of the type of biogas and methanol purification and loading as fuel for a 4-stroke generator on exhaust emissions. An experimental study to test the efficacy of biogas and methanol fuels with or without loading with RON-90 gasoline (Pertalite®). The percentage of carbon monoxide (CO) and hydrocarbon (HC) emissions is used as a reference in assessing the efficacy of fuels in reducing emissions. The results of exhaust emission test studies using biogas purified from H2S, H2O, CO2, and methanol produce exhaust emission values of HC and CO with a lower value compared to the maximum value of the threshold according to the standards of the Minister of Environment Number 05 of 2006 so that biogas purified from H2S, H2O, CO2, and methanol is more environmentally friendly than RON-90 gasoline on the market.